Efficiency Analysis of Public Health Spending in Brazilian Capitals Using Network Data Envelopment Analysis (DEA) - Maria Stella de Castro Lobo; Edson Correia Araujo (The Central European Review of Economics and Management (CEREM), 2017)
Aim: In 1988, Brazil implemented profound changes in the organization and financing of its public health system, with the creation of the Unified Health System (Sistema Unico de Saud́e - SUS), establishing universal health coverage. The gradual expansion of the health system and entitlements to services has been accompanied by the debate about the appropriate level of government spending and health system efficiency.~Design / Research methods:~The study uses VRS - output oriented, Dynamic Network SBM DEA model, period 2008-2013, to depict the relationships that take place between diverse levels of care (primary health care/PHC and secondary-tertiary health care/STC). DMUs are Brazilian state capitals, which implement key health policies and assist patients from smaller surrounding municipalities, especially for STC. Inputs are PHC and STC budgets; outputs are their respective services provided and avoidable deaths. The link variable is PHC medical consultation, entrance door to the system and gatekeeper for more complex levels of care. Dynamic model evaluates efficiency across time.~Conclusions / findings:Overall performance was 0.86; for PHC, 0.90; for STC, 0.85 (SD=0.15). 8 out of 27 capitals were fully efficient. Capitals increased average scores in both levels of care, but only STC had a positive technological change (frontier shift >1). Link variable behavior denotes a bottleneck between levels of care. Projections onto the frontier enable establish own management diagnosis and goals for financing and development.~Originality / value of the article:~Network models mimic hierarchically organized health systems. The appliance of results aids health policy. – – Cel: W 1988 roku Brazylia wdrozẏła dogłebne zmiany w organizacji oraz finansowaniu systemu słuzḃy zdrowia, powołujac do zẏcia Zunifikowany System Opieki Zdrowotnej ("Sistema Unico de Saud́e" - SUS), zakładajacy powszechny dostep do słuzḃy zdrowia. Stopniowemu rozszerzaniu systemu opieki zdrowotnej oraz uprawniend́o usług medycznych towarzyszyła debata dotyczaca odpowiedniego poziomu wydatkoẃ rzadowych i wydajnosći systemu.~Metodyka badan\': W badaniu wykorzystano zmienne efekty skali zorientowane na wyniki, model Slacks-Based-Measure oparty na dynamicznej sieciowej metodzie obwiedni danych (ang.: Data Envelopment Analysis (DEA)) dla danych z lat 2008-2013, aby zobrazowacźalezṅosć\', jaka zachodzi pomiedzy roźṅymi poziomami opieki (podstawowa opieka zdrowotna (ang. primary health care (PHC)) oraz opieka zdrowotna drugiego i trzeciego stopnia (ang. secondary-tertiary health care (STC)). Jednostkami podejmujacymi decyzje sa brazylijskie stolice stanowe, ktoŕe wdrazȧja kluczowe załozėnia polityki zdrowotnej oraz wspieraja pacjentoẃ z okolicznych, mniejszych jednostek administracyjnych, szczegoĺnie w zakresie STC. Nakłady stanowia budzėty PHC i STC, natomiast wynikami sa wynikajace z nich usługi oraz przypadki zagrozėnia zẏcia, w ktoŕych udało sie uratowacṕacjentoẃ. Powiazana zmienna to konsultacje medyczne w ramach PHC, drzwi wejsćiowe do systemu oraz strazṅik bramy do bardziej kompleksowych poziomoẃ opieki. Dynamiczny model pozwala oceniacẃydajnosćẃ czasie.~Wnioski: Ogoĺny stan wyniośł 0,86, przy czym dla PHC kształtował sie na poziomie 0,90, a dla STC 0,85 (SD=0,15). 8 z 27 stolic okazało sie w pełni wydajnych. Stolice zdołały zwiekszycẃyniki w obu poziomach opieki zdrowotnej, ale tylko STC dosẃiadczyło pozytywnej zmiany technologicznej (frontier shift > 1). Zmienna powiazana wykazała waskie gardło pomiedzy poziomami opieki. Projekcje dotyczace granic (frontier shift) pozwoliły ustalicẃłasna diagnoze dotyczaca zarzadzania oraz cele zwiazane z finansowaniem i rozwojem.~Wartosćártykułu: Modele sieciowe nasĺaduja hierarchicznie zorganizowane systemy opieki zdrowotnej. Wykorzystanie wynikoẃ wspiera polityke słuzḃy zdrowia.
Keywords: H21; H51; O10; O54; 330; Network DEA; Efficiency Measurement; Health and Economic Development; Public Health; Health; Education and Welfare; Network DEA